The Effect of Liquid Organic Fertilizer From Tofu Waste and NPK Fertilizer on The Growth of Lettuce (Lactuca sativa L.) - Rahmatia, Nurul Adani; Raksun, Ahmad; Mertha, I Gde (Jurnal Biologi Tropis, 2026)
Lettuce presents significant market potential, catering to both local and global demands. The strong need for this horticultural product gives it considerable economic importance, which can enhance individual earnings. This study intends to evaluate how liquid organic fertilizer made from tofu waste and NPK fertilizer influences the growth of lettuce (Lactuca sativa L.) and to assess how their combination impacts lettuce plants. An experimental method was employed, with data gathered from measuring plant growth. The application of liquid organic fertilizer derived from tofu waste alongside NPK fertilizer notably influenced the height of the plants, the quantity of leaves, the size of leaves, and both the wet and dry weights of the lettuce. In contrast, the interaction between the liquid organic fertilizer from tofu waste and NPK fertilizer did not show a significant impact on the height, number of leaves, leaf size, or the wet and dry weight of the lettuce.